2019
DOI: 10.1159/000502977
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Estradiol and Neuroplasticity in Transgender Women after Gender-Affirming Surgery: A Bimodal Hypothesis

Abstract: For transgender individuals, gender-affirming surgery (GAS) and cross-sex hormone therapy (CSHT) are part of the gender transition process. Scientific evidence supporting the maintenance of CSHT after GAS-related gonadectomy is accumulating. However, few data are available on the impact of CSHT on the brain structure following hypogonadism. Thus, we aimed to investigate links between estradiol and brain cortical thickness (CTh) and cognition in 18 post-gonadectomy transgender women using a longitudinal de-sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Furthermore, our results cannot generalize to ages beyond 12-to 17-years-old. Studies on adults have examined cortical structure related to GD [9,26,[102][103][104][105][106][107][108], but we know of no studies examining cortical structure of GD children. Lastly, we examined three cortical structural brain features; other aspects of adolescent GD brain structure (e.g., white matter microstructure) await investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, our results cannot generalize to ages beyond 12-to 17-years-old. Studies on adults have examined cortical structure related to GD [9,26,[102][103][104][105][106][107][108], but we know of no studies examining cortical structure of GD children. Lastly, we examined three cortical structural brain features; other aspects of adolescent GD brain structure (e.g., white matter microstructure) await investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…As previously reported in the methodology section in Schneider et al [53], venous samples were collected between 8 a.m. and 10 a.m. at each of the time points. E 2 was measured using an electro-chemiluminescence immunoassay (ECLIA; Roche Diagnostics, Mnaheim, Germany) with assay sensitivity of 5.0 pg.mL and intra- and inter-assay CV of 5.7% and 6.8%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Combining nuclear magnetic resonance spectroscopy with clinical and neurocognitive data may provide a more comprehensive understanding of the role of sex hormones in the brain, particularly for their protective or deleterious effects [52]. Recently, our group showed that E 2 replacement in hypogonadal trans women strengthens the functional connectivity between the thalamus and primary sensorimotor cortex and affects cortical thickness in E 2 -receptive brain regions [17, 53]. However, the underlying biochemistry of sex hormones that translates into neuroimaging and its relationship with a neurobiological basis of neurocognition is still unclear.…”
Section: Introductionmentioning
confidence: 99%